(untitled) (Journal of the College of Education for Women, 2019)
The aim of this message to monitor this phenomenon throught the Quran , which is the constitution of the Islamic nation and Hariatha as well as to express kasalah integrity , justice honesty , patience , abd pacr .We feel this vocabulary to hight athical values advocated by the Quran and the need to build commitment to the orthodox society free of corruption that leads ta a disorder of the human society .The outcome of the study the researcher found that faith to a number of results was most notably the advent of righteusness in the Holy Quran meaning of comprehensive RPR spacious field and breadth Maadenh .